Status of population‐based birth defects surveillance programs before and after the Zika public health response in the United States. Issue 19 (19th September 2018) - Anderka, Marlene; Mai, Cara T.; M. Judson, Emily; Langlois, Peter H.; Lupo, Philip J.; Hauser, Kimberlea; Salemi, Jason L.; Correia, Jane; A. Canfield, Mark; Kirby, Russell S.
Abstract : Background: The 2016 Zika public health response in the United States highlighted the need for birth defect surveillance (BDS) programs to collect population‐based data on birth defects potentially related to Zika as rapidly as possible through enhanced case ascertainment and reporting. The National Birth Defects Prevention Network (NBDPN) assessed BDS program activities in the United States before and after the Zika response. Methods: The NBDPN surveyed 54 BDS programs regarding activities before and after the Zika response, lessons learned, and programmatic needs. Follow‐up emails were sent and phone calls were held for programs with incomplete or no response to the online survey. Survey data were cleaned and tallied, and responses to open‐ended questions were placed into best‐fit categories. Results: A 100% response rate was achieved. Of the 54 programs surveyed, 42 reported participation in the Zika public health response that included BDS activities. Programs faced challenges in expanding their surveillance effort given the response requirements but reported mitigating factors such as establishing and enhancing partnerships and program experience with surveillance and clinical activities. Beyond funding, reported program needs included training, surveillance tools/resources, and availability of clinical experts. Conclusions: Existing BDS programs with experience implementing active case‐finding and case verification were able to adapt their surveillance efforts rapidly to collect and report data necessary for the Zika response. Program sustainability for BDS remains challenging; thus, continued support, training, and resource development are important to ensure that the infrastructure built during the Zika response is available for the next public health response.